Pengembangan Flipbook TAMAN “Terpujinya Akhlak Mulia Ahmad Dahlan” pada Pembelajaran PAI Kelas 4 di SDN Babakan Hurip - Ani Nur Aeni; Rohaiphy Aleyda Kana; Ratih Ambar Sari; Amanda Claudia Putri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to test the development of a learning media in the form of an interactive flipbook that can be used to assist teachers in implementing Islamic Education learning for fourth grade elementary school students. This flipbook is designed in accordance with the Core Competencies, Basic Competencies, and Learning Objectives of the “Merdeka'' Curriculum Grade 4 Elementary School Islamic Education book. The material raised in this flipbook is about emulating morals and internalizing moral principles as exemplified by a religious figure named K.H. Ahmad Dahlan. This research applies an R&D (Research and Development) approach or method with the ADDIE research model (Analyze, Design, Development, Implementation and Evaluation). The development technique goes through the stages of needs analysis, design, development, implementation and assessment. The flipbook created has interesting and interactive images that increase students' understanding of the importance of implementing commendable morals in everyday life through a collection of inspiring stories by K.H. Ahmad Dahlan. The subjects in this research were fourth grade students at Babakan Hurip State Elementary School, South Sumedang District, Sumedang City, West Java. Based on the test results, research subjects showed a positive response to the use of flipbooks that had been developed.